2005
DOI: 10.1111/j.1365-2621.2005.tb09032.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PET and PET/PEN Blend Packaging on Ascorbic Acid and Color in Juices Exposed to Fluorescent and UV Light

Abstract: ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: A : A : A : A : Apple and or pple and or pple and or pple and or pple and orange juices packed in poly ange juices packed in poly ange juices packed in poly ange juices packed in poly ange juices packed in polyester bottles w ester bottles w ester bottles w ester bottles w ester bottles wer er er er ere stor e stor e stor e stor e stored in dar ed in dar ed in dar ed in dar ed in dark, intense fluor k, intense fluor k, intense fluor k, intense fluor k, intense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…8,9 Moreover, changes to ascorbic acid levels are influenced by the type of packaging used. 2 Today, PET is the most widely employed packaging for food products and the trend is now to use PET with oxygen scavengers, or PET complexed with nylon or polyethylene naphthalate, 10,11 which have better barrier properties against oxygen and may limit the aerobic degradation of ascorbic acid. However, most of the results obtained when testing various new plastic packaging materials have remained confidential.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Moreover, changes to ascorbic acid levels are influenced by the type of packaging used. 2 Today, PET is the most widely employed packaging for food products and the trend is now to use PET with oxygen scavengers, or PET complexed with nylon or polyethylene naphthalate, 10,11 which have better barrier properties against oxygen and may limit the aerobic degradation of ascorbic acid. However, most of the results obtained when testing various new plastic packaging materials have remained confidential.…”
Section: Introductionmentioning
confidence: 99%
“…Solomon and others 9 did not observe any statistical differences (p < 0.05) between the vitamin C content of orange juice stored in glass at 8°C under artifi cial light (200 lux, three tubes of 40 W) or in darkness. More recently, Conrad and others, 10 with monolayer PET, also found no positive effect of orange juice storage in darkness when compared with storage under artifi cial light; losses of vitamin C being almost identical. For another food product, pasteurized milk, one of the main mechanisms of quality deterioration is light-induced vitamin deg- …”
Section: Vitamin C: Infl Uence Of Artifi Cial Light During Storagementioning
confidence: 90%
“…Sattar and others 7 showed that artifi cial light (540-650 lux) increased the degradation of vitamin C in model orange juice stored in glass bottles at 25°C during 32 days. On the contrary, Mottar, 8 Solomon and others, 9 and Conrad and others 10 did not fi nd any difference between the vitamin C contents of juice stored under artifi cial light and in darkness.…”
Section: Introductionmentioning
confidence: 89%
“…Blending 4% polyethylene naphthalate with PET helps to reduce UV radiation between 322 and 373 nm in storage environments thus helping to preserve color and vitamin C in juices exposed to fluorescent light. 344 Tinuvin 1577 was successfully used to protect surface degradation of PET. 346 The presence of UV absorber reduced formation of carboxyl end-groups.…”
Section: Characteristic Changes and Propertiesmentioning
confidence: 99%